Effects of stem cutting types, position and hormonal factors on rooting in Stevia rebaudiana Bertoni - Abdullateef, Raji Akintunde; Osman, Mohamad (Canadian Center of Science and Education, 2012)
Stevia rebaudiana Bertoni, a compositae, originated from Paraguay. It is propagated by stem cuttings. Leaves’ glycosides are about 300 times sweeter than sugar and safe for diabetic patients. In Malaysia, techniques for stevia mass production are limited. Varieties MS012 and MS007 obtained from MARDI were studied. For each variety, cuttings made were: (i) young apical shoot (ii) old apical shoot and (iii) non apical shoot. They were treated with six concentrations of IBA ranging from 1.9 to 2.5mM, and were placed in micro cutting chambers with the control. Characters studied were: (i) number of days for rooting, and (ii) root number at emergence. Analysis of variance revealed there were significant differences between characters at probability level p < 0.05. Cuttings from young apical shoots of MS012 and MS007 rooted on 5th day with root number ranging from 2.8 to 13.8. IBA 2.3mM was optimal. Young apical cuttings of either variety treated with the IBA 2.3mM were ideal.